Activation by 9-(R)-[2-(Phosphonomethoxy)Propyl]Adenine of Chemokine (RANTES, Macrophage Inflammatory Protein 1α) and Cytokine (Tumor Necrosis Factor Alpha, Interleukin-10 [IL-10], IL-1β) Production - Zídek, Zdenĕk (American Society for Microbiology, 2001)
Development of a novel group of antiviral agents, acyclic nucleoside phosphonates, has provided a new perspective for treating human immunodeficiency virus (HIV) infection. One of the compounds, 9-(R)-[2-(phosphonomethoxy)propyl]adenine (PMPA) (tenofovir), has been shown to confer complete protection against AIDS in a simian model of the infection. The aim of our study was to investigate whether the antiviral efficacy of PMPA, which depends mainly on inhibition of virus-induced DNA polymerase or of reverse transcriptase, could be contributed by immunomodulatory potential of this drug. We screened for its ability to activate production of cytokines and chemokines that are known to interfere with the replication and/or the entry of HIV in cells. Using the in vitro test system of mouse macrophages and lymphocytes, it has been found that PMPA stimulates macrophage secretion of interleukin-1β (IL-1β), IL-10, and tumor necrosis factor alpha. Production of the chemokines RANTES and macrophage inflammatory protein 1α was activated in both macrophages and lymphocytes, and also in human cell line U937. Other cytokines—i.e., IL-2, IL-12, IL-13, and gamma interferon—remained uninfluenced by PMPA. The cytokines were stimulated in a dose-dependent fashion, with rapid onset, and peak concentrations were achieved within 5 to 24 h. The findings contribute to a more complex understanding of mechanisms of antiviral effectiveness of PMPA and support the view that this drug could become a promising candidate for therapeutic exploitation in anti-HIV preventive medicine.